ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING PADA PRODUK JASA GOJEK - Aldila Sahura; Manuntun Pakpahan; Dewi Nurmasari Pane (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The research analysis aims to find out whether service quality and brand image simultaneously have a positive and significant effect on consumer satisfaction with Gojek service products (case study of 2020 stambuk management students at Panca Budi Development University, Medan. The data analysis technique used is an associative research method with the help of the SPSS program . This research uses path analysis. The sample in this research is 96 respondents. Primary data collection using a questionnaire shows that service quality partially has a positive and significant effect on the brand image of Gojek service products (case study of Stambuk Management Students 2020 at Panca Development University. Budi Medan. Service quality partially has a positive and significant effect on consumer satisfaction with Gojek service products (case study of Stambuk management students 2020 Panca Development University Budi Medan. Brand image partially has a positive and significant effect on consumer satisfaction with Gojek service products (student case study 2020 stambuk management, Panca Budi Development University, Medan. Service quality and brand image simultaneously have a positive and significant effect on consumer satisfaction with Gojek service products (case study of 2020 stambuk management students at Panca Budi Development University, Medan. Service quality has a positive and significant effect on consumer satisfaction with brand image as an intervening variable in Gojek service products (case study of 2020 stambuk management students at Panca Budi Development University, Medan.